COCO’S IDENTITY CRISIS AND LOVE IN WEI HUI’S SHANGHAI BABY (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
COCO’S IDENTITY CRISIS AND LOVE IN WEI HUI’S SHANGHAI BABY Rosandina Amalia English Literature, Faculty of Languages and Arts, Surabaya State University Ochan.strezz@gmail.com Drs. Much. Khoiri, M.Si English Department, Faculty of Languages and Arts, Surabaya State University much_choiri@yahoo.com Abstrak Identity adalah tanda seseorang untuk membuat mereka berbeda dari yang lain. Dalam hal perbedaan, sering menjadi krisis bagi mereka yang tidak bisa mengendalikan identitas mereka. Mereka mengalami identity crisis; itu adalah masalah yang membawa orang ke jalan yang sesat. Ada begitu banyak faktor yang menyebabkan krisis ini; dalam penelitian ini salah satu faktor terbesar adalah love. Selain itu, love adalah akar dari identitas masyarakat karena itu adalah pusat untuk mengenali diri mereka dan juga orang lain. Penelitian ini memfokuskan pada identity crisis Coco dan pengaruh love yang dapat mempengaruhi identity crisisnya di Wei Hui Shanghai Baby. Tujuan dari penelitian ini adalah untuk mengidentifikasi identity crisis Coco di Wei hui Shanghai Baby dan menganalisis love Coco yang mempengaruhi identity crisisnya. Penelitian ini menggunakan dua teori, identity crisis mengacu pada teori Erikson yang menunjukkan gejala identity crisis. Teori love yang mempengaruhi identity crisis diambil dari Robert. J. Stenberg. Hasil analisis menunjukkan bahwa identity crisis Coco memiliki dua gejala; mereka adalah kebingungan peran dan keintiman. Identity crisis Coco itu sendiri disebabkan oleh love. Love memiliki tiga komponen-keintiman, gairah dan komitmen-dan masing-masing komponen memiliki empat jenis yang menjadi pembangunan komponen tersebut. Pengaruh identity crisis pada Coco memiliki semua komponen love. Terakhir dari semua, identity crisis adalah gangguan yang dapat menyebabkan seseorang untuk menuju ke jalan yang sesat, dengan cara yang berlebihan. Kelebihan ini membuat orang memaksa diri mereka untuk menutupi semua kebutuhan itu, termasuk love. Dengan demikian, love bisa menjadi aspek untuk pembangunan sebuah identity. Kata kunci: identity, identity crisis and love Abstract Identity is the sign of someone to make it different from another. In terms of differences, it often becomes a crisis for those who can not control their identity. They face an identity crisis; it is the problems that bring people into an astray way. There are so many factors that lead this crisis; in this study one of the biggest factors is love. Additionally, love is the root of people’s identity because it is the ground to recognize their self and also someone else. This study focuses on Coco’s identity crisis and the influences of love that can influence her identity crisis in Wei Hui’s Shanghai Baby. The purpose of this study is to identify Coco’s identity crisis in Wei hui’s Shanghai Baby and to analyze the way Coco’s love influences her identity crisis. This study uses two theories, the identity crisis refers to Erikson’s theory that shows the symptoms of identity crisis. The theory of love that influences the identity crisis is taken from Robert. J. Stenberg. The result of the analysis shows that Coco’s identity crisis has two symptoms; they are role confusion and intimacy. Coco’s identity crisis itself is caused by love. Love has three components—intimacy, passion and commitment—and each component has four types that become the construction of the components. Coco’s influence of identity crisis has all of the components of love. Last of all, identity crisis is the disorder that can lead someone to an astray way, an excessive manner. This excess makes people force their selves to cover all of the necessity, including love. Thus, love can be an aspect for the construction of an identity. Keywords: identity, identity crisis, and love. INTRODUCTION Identity is one of the most favourable themes because it is the parts of human life. Identity is ubiquitous in contemporary of social value, cutting across psychoanalysis, psychology, sciences, history, politics, culture and also sociology. Identity is defined as all information associated with an individual or organization. It defined a set of meaning applied to the self in a social role or situation defining what it means to be who one is (Jacobson, 2003: 3). The relative usages of identity is in terms of the essential to the culture of a people, to common identification with a collectivity or a social category, also in contemporary works on social movement, thus creating a common culture among participants. Individual, ethnic, national, transnational are the instructors of the identity hierarchy that some of them are acquisitive and selective whereas some of them are non-acquisitive, depending on the structure and circumstances person’s opportunity. Identity crisis is a universal issues and each of every person can actually experiences the crisis. Identity crisis is the reflection of person life that can make them stronger or even weakness in the identity. Identity crisis is one of the biggest problems for human life because it brings people that face it into an astray way. Another thing is that people that have an identity crisis will have an excessive to something. They will have something pleonastic to something that they think its important and can make them happy, comfortable and also feeling better. It means people who have the identity crisis will do something that can make their self happy even its too much and they never care about what other people thought about her/him as long as they satisfied about something that they need. So, the identity crisis is the identity problem of a person that brings them into an astray way, an awkward character and even an excessive to something. Its interesting when Shanghai Baby (1999) by Wei Hui has much controversy in Chinese culture and beyond in the earlier of millennium era, because it is generally a taboo novel in People’s Republic of China (PRC). It is rightfully banned in China because of its controversy, things that make it becomes as the controversy is not only about the audacious topics such as sex, pornography portrayed, desire and all taboo subjects in Chinese literature, cultural criticism imagine and also the construct tension between a gender, race and ethnicity. It is about a young urban woman leading a wild and an extravagant lifestyle. Her high desire to her couple makes her forget for a while about her identity as a Chinese woman. These presences of the love and the identity crisis of a woman as the main character in the novel, Coco, indeed, are portrayed clearly. The love in this novel is something that can make the main character in the novel has the crisis in her identity. Love is the one that has a big influenced to find the right identity. It depends on the people that choose the love. Love can control everything, include the identity of a person. The crisis of a person can show by their character to the people and the society around. People that usually have a problem with their identity, they have an identity crisis inside their identity. In Wei Hui’s Shanghai Baby, the main character here is a woman named Coco, 25 years old. Her real name is actually Nikky, but she called Coco because her idol named Coco Chanel. She is a waitress but she is also a writer for her novel but she still does not finish her literary works until she meet with a guy named Tian Tian. Then he becomes Coco’s boyfriend but he is an impotent boyfriend which leads her to another man because Tian Tian can not give her the satisfaction in her sexuality. Coco feels so frustration because she can not get her satisfaction with her boyfriend. This brings her to the other man named Mark. He is a foreign guy from Germany. He only becomes a man that will give her the satisfaction in the bed. Beside she had a frustration with her boyfriend, she also faced a role confusion which makes her has only limited friends. She also often isolates her self alone in the apartment of her boyfriend that she placed it to finish her novel. Furthermore, she has an intimacy with her 2 lover, whether from her real boyfriend and also from her affair man. Because she is a writer, she also has a good imagination of something, but she also can not distinguish which one is the imagination and which one is the reality. Her dreams is always blows her up, it brings her everywhere until she goes everywhere that she did know where should she go and what should she did. She confused which man than she loves. The ending of the story is so ironic which is her Germany lover should back and live forever in Berlin and after that not long after the leaving of Mark, her beloved Tian Tian death cause of he consumed drugs. Coco finally decided to go to Berlin to publish her novel. Coco loses her lovers, both of them but she still alive even she only has a limited power to live. It gives clear portrayed that Coco has a problem with her identity, especially with her love identity. She can not choose the man that she loves because she loves both of them while the balance in life is people should choose only one person to be our lover, to be the one only that can share a future together. In accordance of background study above, it can be simplify to discuss among two problems that emerge as significant concern toward this novel. How is Coco’s identity crisis reflected in Wei Hui’s Shanghai baby? How does Coco’s love influence her identity crisis in Wei Hui’s Shanghai baby? Based on all of the facts above, this study intended to a key which is about the human identity crisis by one of the post-Freudian theories, Erik H Erikson. Beside the theory of identity crisis, it uses the theory of love to give a clear explanation about Coco’s love that influences her into the crisis of the identity. The love theories come from Robert Stenberg that has 3 main components of love that related to the main character in the novel to solve the statements of problems. RESEARCH METHOD It must be a data in every researches, even the literary research has a data. The data is not contains of a numeric data but it contains of a qualitative data which emerge a fascination to interpret literary works. Qualitative data are attractive. They are sources of well-grounded rich description, and explanation of processes occurring in local context (Miles and Huberman, 1984: 11). It means that the qualitative data in literary research indeed more interesting because it contains of a deep and clearly explanation and description about the literary works as an object of the data. Here, it will present the data from 2 kinds of classify, they are: Data Source Data source is a subject of the research. There will be 2 kinds of data sources, first is the primer data. It takes from the subjects of the research. The concrete data sources that will be used in this thesis is the novel itself, entitled Shanghai Baby by Wei Hui. It published in 1999. It will envolves quotations, fragments and dialogues or monologues that indicate the factors and the resolution leading to Coco’s identity crisis and her love. And the second is secondary data which can take from many kinds of books, journal, magazine, previous studies about the related topic. It also puts to the references where the researcher finds the secondary data. Data Collection During the collected of the data, the researcher had read the novel as the subjects, comprehend the contents of the novel and also understand about the concepts of the topic. It called as the library research. Analysis during data collection lets the fieldworker cycle back and forth between thinking about the existing data and generating strategies for collecting new-often better quality data (Miles and Huberman, 1984: 49). It means an extensively and intensively close reading through to the novel. And then finding some proper quotations which are used to reveal the main idea of the novel that emerge the identity crisis of the main character in the novel. The data collection will have a long process during the research as long as the researcher feels that the data is accurate or not. The researcher will move forward and even move back again to make the research becomes better. ANALYSIS The first section is about Coco’s identity crisis. the related theory of identity crisis comes from Erik H. Erikson. It decided into 8 stages and each stage has a psychosocial crisis (Erikson, 1974: 90). The psychosocial crisis is symptoms that every stage of age will have the different crisis. There are many symptoms that emerge an identity crisis, such as shame and doubt, guilty feeling, inferiority, role confusion, intimacy and isolation, self-absorption, and despair. In this case, Coco’s character emerge two symptoms that really related to the crisis. They are role confusion that has in the fifth stage and then an intimacy that put in the sixth stage which in the adulthood. Role confusion is the act of confusing or the state of being confused. As Erikson said that human experience an identity confusion in an area’s, such as career, and some path areas of interest choice of friends relationship and etc (Erikson, 1974: 93). Role confusion is the act of confusing or the state of being confused. As Erikson said that human experience an identity confusion in an area’s, such as career, and some path areas of interest choice of friends relationship and etc (Erikson, 1974: 93). I sat on the sofa, my hand cradling my head, asking myself if I really understood myself as a woman. Was I really attractive? Wasn’t I a bit hypocritical, snobbish, and fuzzy minded, too? The problems of my life stacked up one on another, and it would take an entire lifetime just to overcome them. (Weihui, 1999: 105) When she is alone while holding her head, she often thought about something. Even it is about her self, another thing about life, her fantasized and she always has a thought about something when she is in a lonely circumstances. In this time, she thought about her self as a woman. She is still in a confused condition with her gender as a real woman. It gives the real fact that her confusion about her minds. She is confused about her characteristic as a woman. She thought that she is a woman but she still can’t understand about her self as a woman. She even can’t choose who really she is. She actually has the quality of attracting to the men. She is a charming woman. But, she is still confused about that. Whether she is a woman with a certain character or not she still does not know well about it. “Wasn’t I a bit hypocritical, snobbish, and fuzzy minded, too?” (Weihui, 1999: 105). She told to her mind that is she a liar, hypocrite, or even a person that has a big heart but really likes to show off to everyone, and also between her fussy minded that talks too much. It is so complicated problem for her. She faces a professing feelings or virtues one does not have. She has a characteristic of those who incline to social exclusiveness and who rebuff the advances of people considered inferior. This is the causes of her problem that stacked and being mess up. “I didn’t know what to do, what day it was, or who I was” (Weihui, 1999: 239). She never be a normal person if she still has a fussy minded and confusion about her self. For instance, she always has confusion between her self. One day, when she has no friends in her apartment, she has nothing to do, not even has a plan to go out to do something. But she also confused what day is that and who really she is. Her problems will overcome to her as her fussy minded emerge. “Agitated, I circled the room. At last, I decided I had to leave the apartment, for where I didn’t know, but I had money in my handbag and my face was made up.” (Weihui, 1999: 105). She is a fussy minded but sometimes she also has a nothing thought. It proves when there is no one in her room, she decided to leave. But she even does not know about where she would go after she is leaving her room. Her mind told that as long as she had enough money, she can go everywhere she likes. She is totally out of focus of something. She can not focus only in one way, to finish her novel. “I’m in Beijing,” I said, as my heart was seized by a sharp wave of tired tenderness. I didn’t even know why I was in Beijing at this moment.” (Weihui, 1999: 111). After she circled her room, she decided to go to Beijing to meet her old friend. She went there only for spending her time, not to be alone and lonely in the apartment. But, she actually didn’t know exactly what her purpose to go to Beijing. It was so useless when she told to Tian Tian on the phone. This really shows that her minds is still wishy washy. She even didn’t know about the place that she went at that time. The second role confusion is between a woman in the real life or as the writer in the unreliable life. Her grandmother decided what she wants to be in the future. In fact, it was my grandmother who predicted that I would be a writer. With a literary star shining down on me and a belly full of ink, I would, she said, make my mark one day. (Weihui, 1999: 18). By the predicted of her grandmother, Coco’s feeling had been hypnotic that she will be a writer. She fetch up all standing by her grandmother’s predicted. “Coco, I’ve got an idea,” he said. “What idea?” “Why don’t you give up you job at the cafe?” Tian Tian said. “Then what would I do?”. “We have enough money, not to have work all the time. You could write your novel.” (Weihui, 1999: 6) In a time, when she mets Tian Tian at the first time and Tian Tian asked her to be a writer, she suddenly agreed with that decision without thinking about another risk. Actually, she had already made a several job, it is in the magazine company publisher and also she had already wrote a several short stories but it didn’t make succeed. That is the causes she quits become a writer until she met Tian Tian. She started to write again as Tian Tian grant to her. Tian Tian asks Coco to become a writer again because he trusts Coco that she can write again. It brings the clear explanation that she still uncertain about her ability to be a writer. After she met Tian Tian that makes her ability suddenly appear again. “From the moment I first saw you at green stalk, I just feel you were cut out to be writer.” Tian Tian went on (Weihui, 1999: 23). As Tian Tian said that he totally sure that Coco’s life were being set as a writer. He saw Coco at the first time when she done her job in Green stalk cafe. Started at that time, Tian Tian saw Coco that she is correctly to set as being a writer. But she still uncertainty about her self to be a writer. The novel had brought me in a worry. I didn’t know how to disguise myself effectively to my readers. In other words, I didn’t want to mix my novel up with my real life and to be honest, I was even more worried that as the plot developed, it could have an impact for my future. (Weihui, 1999: 92) This is become her trouble to become a famous author. The novel that she wrote, she had to be an invisible woman. She had to separate between herself in the real life with her self in her novel. She needs to modify the manner in order to conceal her identity of her character in the novel. Because if she wrote her real life in the works, people thought about her life is abnormal. By the time she felt so worry if she went so far. She feels truly sad and becomes so pessimistic about her novel. Her pessimistic appears since her novel did not make any significant change or even she has no feeling that her novel will become a sensational novel or she will become a famous author. She even more worries when she can’t distinguish her real life that proper to be written in her works. It gives an impact in her future, what is the impact of it she still does not know about it. Who knows what the future brings, but she has to avoid the bad things happen in her life. The way to avoid the bad thing is not to invoke her real life in her novel that she wrote. She wants to be a writer but not to write about her real life as public consumptions. Another thing that can appear her spirit to become a writer is her psychologist, David. He is not only suggested her as a writer but also give a value to Coco’s character. The third Coco’s role confusion comes from her love. She has two different characteristics of her lover. Between her real love Tian Tian and also her affair Mark. After she quits from her job in the Green Stalk cafe and her parents forbid her to live in Tian Tian’s apartment, she gets so out of control. She meets with the Germany man in her friend party, Madonna. The Germany man named Mark. Mark’s abilities seemed to have been a gift from the gods, whereas Tian Tian was the total opposite. They were like beings from two different universes. Their existences met in inverted images of themselves projected onto my body (Weihui, 1999: 177). Her role confusion to choose between Mark and Tian Tian started when all of them show their differences. Mark has so much abilities and much power to attrack his opposite. He is also a business man that has so much relation everywhere. He is a business man that work for a while in Shanghai. Tian Tian just couldn’t handle sex. I’m not sure if it was related to the tragedy that caused his mental problems, but I remember the first time I held him in bed. When I discovered he was impotent, I was devastated, so much so that I didn’t know if I could stay with him. Ever since college I had seen sex as a basic necessity (although I’ve since changed my mind about this). (Weihui, 1999: 5) In that quotation shows that the men named Tian Tian is Coco’s boyfriend that she just recognised him not too long. Tian Tian also has a problem with his identity because his background of his life is not really good. “Grandmother was convinced it was murder. My dad didn’t have any history of heart disease; she said my mother killed him. That she had another man over there, and they plotted it together” (Weihui, 1999: 3). In addition, the background life of Tian Tian is because of the mystery death of his father and the unfaithful mother. But, he still does not believe her grandmother, it can probably true. These bring his silent and cool characterisation in his daily life. “Tian Tian just couldn’t handle sex” (Weihui, 1999: 5) from the quotation, it gives clear description that Tian Tian has a trouble with his sex ability. He can not handle his lust even he has a trouble with his sex ability. He is an impotent, but Coco does not know the cause of his impotent. “I’m not sure if it was related to the tragedy that caused his mental problems, but I remember the first time I held him in bed” (Weihui, 1999: 5). Perhaps, it has a relation to his mental tragedy that caused his mental problem. That is the causes of his impotent. He has no desire to a women, Coco is the one that he loves much. In the other hand, Coco feels disappointed with the sexual of Tian Tian. “I was devastated, so much so that I didn’t know if I could stay with him” (WeiHui, 1999: 5). Until she is speechless to lay waste and think about what should she does for the next after she knew he was an impotent. If it takes a look to the Erikson stages, this case has a problem with Coco’s love that has in the sixth stage. The sixth stage believed that love could become something that heal everything, include the crisis of identity. But, in this case, it would never happen because the cause of the crisis itself is love. Coco’s feeling is so shatter when she knows that her lover can not give her a satisfaction. Coco has a big lust to a man that she loves. “Ever since college I had seen sex as a basic necessity (although I’ve since changed my mind about this)” (Weihui, 1999: 5). It shows when she was in the college, she really likes sex and she makes sex as her necessary in her life even she tried to handle this but she can’t. In this case, she has role confusion in her adolescence period that can cause the refusal from the society because of her attitude. It proves in her last sentence. Furthermore, for her sex is her basic necessity, it is also for everyone. She has a life compulsion. As it mentions, she needs a sexual satisfaction to give her alive and defend her self. “The man I love can’t give me a sexual satisfaction, and worse, he can’t give me a sense of security. He smokes drugs, and he’s disengaged from the world. Now he’s carried his kitten off to the south, and it seems as if he could leave me at any time. I mean forever. Meanwhile, a married man is giving me physical satisfaction but has no impact on my emotions. We use our bodies to interact and rely on them to sense each other’s existence, but they’re also a protective layer between us, keeping us from connecting mentally” (Weihui, 1999: 104) That is all of her explanation to her psychologist, David. It is clear enough that she really has a serious trouble with her life, the people that she loves. Her first serious problem is with her real love, Tian Tian. He can’t give her satisfaction in the bed. She is lack of the gratification of a desire’s needed. She is insecure from many bad things around because Tian Tian can’t save her. He unconnected him self from something that holds fast and entangles. He is a serious drugs smoker. He is also alienate him self from the world. He really likes to be alone and push him self away from people. This is really bad for Coco that has an ambition’s character. Another side comes from her affair. Mark is a husband from a Germany woman. But Coco felt satisfaction with Mark. He gives too much about a lust to Coco. Unfortunately she has no emotion to Mark, even it is only about caring him even less for loving him. He is capable of giving protection to Coco but she only relies on Mark’s body to give her a satisfaction in the bed. She only separates herself with Mark as a sex partner to give a mental satisfaction. Her purpose to hang affair with Mark is only to give her alive. Without a lust from the man, Coco’s feeling will be so wild because she can’t life without a sex from a man. Without sex, she is never being an existed woman. She is really in trouble. As it mentions in the first paragraph, “ever since college I had seen sex as a basic necessity (although I’ve since changed my mind about this).” (Weihui, 1999: 5). This novel has a thick relation to love. Love is something that Coco’s need to life alive. Indeed, she has so many people around that really love her so much. But, she needs the special person to love her, to share her life together for her future. Sometimes, love can become the cause of someone’s problem. It becomes the causes of an identity, characteristics and also another psychological problem. In this case, Coco faces an identity problem that influenced by her love. Intimacy love appears because of there is comfortable feeling, ability to intimate a relationship between people. Intimacy as the component to create a love, intimacy emerges in the Coco’s love. There are also several types of love that will make this intimacy appears. They are types of liking as a friendship, romantic love, companionate love, and also consummate love. All of those types emerge in Coco’s love. For the first types of love in this intimacy is the type of liking as a friendship. It only happens between her friends, Madonna. As she knows her not too much from Tian Tian, she spends not too much time with her. But one day, they spend a couple days to share about their love in warmth. “Poor you! Your worries have used up all your endorphins. You need to watch your health!” (Weihui, 1999: 173). It shows when Madonna feels so worry about Coco’s condition because of her bad mood circumstances. She tired in her worries about her novel. Until, she spends a week to write a lot, finish her novel until she never gets out form her room. She needs refresh her mind, then Madonna comes and stays there. That’s what a friend for. The next type of love that emerges her identity crisis is the type of companionate. Companionate of love occurs in the family, when there is a big commitment but has no passion at all. Coco’s commitment to her family is about her life as being a good woman in front of her family. A well-manner man, he spoiled me from the start. By the time I was three, he had trained me to appreciate operas such as La Boheme. He always worried that when I grew up I’d lose my body and soul to a sex maniac. I’m his most precious baby, he says, and I should treat men cautiously and never shed tears over them. (Weihui, 1999: 19) This fact shows that she doesn’t grow as a good woman as the wishing of her parents. Her family had reined her to become a good woman. But her parents are totally go in the wrong way. Her father comes from a well manner man contains of a lot of knowledge as the lecture in one of the university in Shanghai. He is so worried about her daughter. When Coco still in the three years old, he often brought her to see an appreciate opera such as La Boheme. He thought that it would trained her about how to be a good woman. But, that’s all about her father’s efforts is totally useless. She won’t to disappoint her father, and she hides her real self in front of her family. As long as she doesn’t make them cry or disappointed, she still stay calm in front of them. Even thought she has no one to share about her boyfriend, about her novel and even about all of the whole cruel life that she faced. The next type of love in this intimacy is the romantic love. The deepest love comes from Tian Tian, a man younger than her. Their introduction from one to each other is too fast. Until, that is, the day he gave me a note said “I love you” along with his name and address.” (Weihui, 1999: 2). It’s clearly enough that Tian Tian falling in love with Coco at his first sight when Coco still does a job in the cafe. He directly gives her a note that he loves her by not saying any words or even knowing her name. “I don’t know why. I just wanted you to make love to me perfectly just once. I want you so much, because I love you.” (Weihui, 1999: 245). The strength of romantic love appears. Romantic love also has a passion beside the intimacy to the closeness. Even she has an impotent boyfriend, but she still wants to heal her boyfriend. Her statement proves that she really loves her boyfriend even she has to convey to herself that he never has sex with her. This leads her intimacy to another man that can satisfied her. She really wants him to be a normal person in order to feel the real sex from the one that she really begs on her life. This passion brings her to the deepest romantic love. The passion’s component of love is one of the parts that take much in this novel. It has a lot of impact to Coco’s identity crisis because of this component of love. There are types of love that can be the shape of passion. They are infatuation love, fatuous love and also romantic love. As it explained in the previous chapter, infatuation love is a love at the first sight and also a crazy love because of something that interact people to stay with their couple. In this case, Coco also faced love at the first sight to Mark. “His eyes were shining in the darkness, like those of an animal lurking in the shrubbery. I was surprised by the feeling those eyes gave me.” (Weihui, 1999: 29). She suddenly feels so attracted by Mark’s gaze on her. His eyes is so glistening with his sharp sight. She feels like she has no power at all not to look his eyes stared at her. This is the symbol of the love at the first sight to Mark. Started her meeting with Mark, she begins affair from Tian Tian. Her first sight to Mark is the inception of her problem with her confusing love, confusing identity and confusing her intimacy. While her fatuous love started when she was in a college. Coco’s infatuation love emerges when she was in college. It shows that she has a big lust since she was in her college. She told about her crazy boyfriend. He is the person that teaches Coco about sex. Started at that time, she has a big lust, a high desire to the man that she loves. “My ex just happened to cater to several of those dispositions, from dependence to masochism to narcissism, and my need to atone to my mother for my sins would be an emotional theme throughout my life.” (Weihui, 1999: 35). He leads Coco to the bad characteristic. Masochism brings Coco to an abnormal condition in which pleasure, especially sexual pleasure, is derived from pain or from humiliation, domination by her ex boyfriend. She has the tendency to derive sexual gratification, from being physically or emotionally abused. Romantic love from Coco between her relationship with Tian Tian and also her affair with Mark is appears. She is deliberately behaves in such a way as to attract attention from Tian Tian. She performs dangerous stunts to attract attention and also a compulsive desire to expose her genitals. He showed no pity, never stopping for a second. The pain burst into a kind of apoplexy. “I opened my eyes wide and looked at him, half in love, half in hate. I was aroused by his naked white body.” (Weihui, 1999: 63). It happens when they had a sex. Mark is really lustful to Coco, he until didn’t give Coco a chances to take a breath. He has no compassion to Coco because he is in the top of his lust. He had a sex with Coco such a fit of an extreme anger to her. He is just like loss of his consciousness. She also stimulated her sexual desire by Mark’s body. She feels a great sexual desire with Mark. “That very night he successfully improved his knowledge of me, from my breast down to my toes, from my heavy breathing to my loud cries.” (Weihui, 1999: 69). Until, Coco feels so satisfied with Mark’s act in the bed. She is really enjoying that sexual affair. I promised Tian Tian I would visit him often and that I would take a good care Fur Ball and myself. I would write seriously and finish my novel. I wouldn’t let myself sink into nightmares. I had to believe I was the luckiest and most beautiful woman alive and that miracles do happen. It was all I could do. I swore I would await his return. I love you. And that’s how my love is (Weihui, 1999: 165). Fatuous love is love pushes by desire and also a commitment to go to the future, it is marriage. This happens between Tian Tian and Coco. Coco wants Tian Tian to go to the Reproduction Healthy Centre because she really wants him to recover him self. It means that she really hopes to Tian Tian’s health. She really cares to Tian Tian but Tian Tian never cares about his health. Beside Tian Tian has a problem with his genital, he is an impotent, he is also a drugs user. He becomes so drugs user when he was far away from Coco. He took morphine. Unfortunately, he doesn’t realize that Coco wants him so much in the future. Beside her care to Tian Tian is too much, she also has a commitment to her self that she will finish her novel. Her novel is the only hopes for Tian Tian’s life. She wants to grant Tian Tian’s hope. She won’t disappoint him. Her commitment here will bring her to the spirit of a life instinct, so does Tian Tian. Commitment love also has a several type of love that built this component. They are an empty love, companionate love, fatuous love and the last is consummate love. The companionate love and fatuous love had been discussed in the previous component of love. They also emerge the strong commitment. an empty love appears because of a compulsion from someone. Even a strong love suddenly can become an empty love because of the broken role of a relationship, but it still has a commit through to the future. In the commitment component, Tian Tian had to fix him self to life with Coco but he had no responsibility to her. While the opposite happens to Coco, she had to take a full responsibility to Tian Tian because he has not much friends to share, dissociable from her family and also his society around. She has to be more carefully also to Tian Tian because he consumes morphine too much everyday. “For no good reason, I felt responsible for him – and also a sense of remorse.” (Weihui, 1999: 23). She feels a sense of deep regret and guilt for some misdeed. She has to be more patient and has a strong enough emotion to face Tian Tian’s character as being a drug user. Coco also is a woman that has a strong desire for success or achievement. He describes Coco is a person who wishes to rise above her present position or condition. She has full of power to be a success woman that has an enough effort for her better life. She is also a loyalty person to her future. From all of Coco’s power to be a success woman, it gives an impact to Tian Tian. He has to commit to him self that he has to be alive because of Coco. He stated to him self of being committed or pledged to Coco that he had to have a good effort for his better future. In order to convince Coco about his committed. CONCLUSION In Wei Hui, Shanghai Baby, the main character is Coco. She has an identity crisis and it influences by her love. As the identity emerges problem for Coco, it followed by the appearing of 2 statements of analysis in this study. Therefore, based from all of the recent analysis of the data, the result can be concluded that there are two conclusions. Firstly, she has a different character because in her previous period she can’t choose a certain identity for her self. She has a problem with her identity. If an identity can’t be the people’s necessity, they will out of control and have a divergent in their identity. It called as an identity crisis. She faces an identity crisis with the role confusion and also an intimacy. Her role confusion emerges between her profession as a writer and also her self as a woman. She can’t choose which one that will be the most important for her life. She is a writer, she also has a good imagination of something, but she can not distinguish which one is the imagination and which one is the reality. Her dreams is always blows her up, it brings her everywhere until she goes everywhere that she did know where should she go and what should she did. Her role confusion emerges because of her lover too. She has 2 lover, but her real lover is an impotent while another one is a foreigner from German. This brings her a sexual disorder with her boyfriend, Tian Tian while Tian Tian is an impotent. She can not choose which one is the best for her. So, her choice is just only depending on her 2 lover whether Tian Tian will leave her or Mark that leave her away. Whereas her intimacy between 2 lover run well, she has no problem when she met with Mark. She can not get what she wants from Tian Tian. Mark only becomes a man that will give her the satisfaction in the bed. She does an affair with Mark, she really satisfied with Mark but she won’t to fall in love with Mark because she still has Tian Tian. Even she has Tian Tian, he can’t give her the best secure for her, lack of attention because Tian Tian is too busy with his morphine. She can not choose the man that she loves because she loves both of them while the balance in life is people should choose only one person to be our lover, to be the one only that can share a future together. Secondly, an identity crisis appears because of many factors. Actually the identity can go weakness because of the society around. Identity of someone sometimes annoys by many factors. The biggest factor from this novel that emerges the identity crisis is because of love. Love is a general way to healing something. But in this case, love becomes a trouble for Coco’s identity. There are components of love that leads Coco to her identity problem. Her love contains of an intimacy, passion and also a big commitment for her future. All of the components appear a trouble for her life in searching for her identity about her self as a woman or as a writer. In every components of love, it has a several types of love that built becomes one strong component. The deepest love of Coco is only to Tian Tian but he can’t give the satisfactions to her. This leads her to affair with Mark. She breaks the law of faithful, this brings her minds so blind until she can not think about what the future brings. She makes a relationship without thought what are the consequences that emerge by her relationship. Love needs a sacrifice to get the immortality of it. Tian Tian sacrificed his love to affair with another man even he knew it exactly what her lover did behind him, he still did not care much about it. He realizes that he can not give her the satisfaction. As final words, love can emerge not only as a happiness for people who feels it but also it can be a trouble for people who has not understanding well about their identity. Everybody wants the love and to be loved by people around. Love also can emerge the crisis of identity. REFERENCE Alwisol. (2009). Psychology Kepribadian. Malang: UMM Press. Arkoff. Abe, (2006). Psychology and Personal Growth. Allyn and Bacon Burns, D. D., (1985), Intimate Connections: The Clinically Proven Program for Making Close Friends and Finding a Love Partner. New York: Signet (paperback) Erikson, E. H. (1950). Childhood and Society. New York. _________. (1968). Dimensions of a New Identity. New York. _________. (1974). Identify: Youth and Crisis. Norton; New York. _________. (1964). Insight and Responsibility. New York. _________. (1975). Life History and Historical Movement. Norton: New York. Ellis, A. (1954), The American Sexual Tragedy. Michigian University: L Stuart Feist, Jess, & Feist, J. Gregory. (2006). Theories of Personality. New York: The McGraw Hill Hall, C. S., Lindsey, G., Wiley, J., & Barbara, S. (1978). Theories of Personality. Toronto: Chichester Brisbane. Hurlock, Elizabeth, B., (1974), Personality Development, New York: McGraw Hill Book Company Hodge, M. B. (1967). Your Fear of Love, Garden City, NY: Dolphin (Doubleday) Klein, G. (1976). Psychoanalytic Theory: An Exploration of Essential. New York: International Universities Press. Maddi, Salvatore, R, (1968), Personality Theories, Illunoise: The Dorty Press Marcia, J. E. (1980) Identity in adolescence. In J. Adelson (Ed.), Handbook of Adolescent Psychology. New York: Wiley, 237-253 Miles, M., & Huberman, A. M. (1984). Qualitative Data Analysis: A Source Book of a New Methods. London: Sage Publication. Monks, F., Knoers, A., & Haditono, S. R. (1992). Psychology Perkembangan: Pengantar Dalam Berbagai Bagiannya. Yogyakarta: Gadjah Mada University Press. Pervin, Lawrence, A., (1984), Personality: Theory and Research, New York: John Wiley and Sons, Inc Rogers, C. R. (1961) On Becoming a Person. Boston: Houghton Mifflin Santrock, J. W. (1993). Adolescence. Dubuque, IA: Brown & Benchmark. Sarwono, S. (2007). Psychology Remaja. Jakarta: PT. Raja Grafindo Persada. Siegel, B. S. (1990), Peace, Love and Healing, New York: Perrennial Library. (paperback) Sternberg, R. J. (1986). A triangular theory of love. Psychological Review, 93, 119-135. Stenberg, R. J., & Barnes, M, L. (Eds). (1988). The Psychology of Love, New Haven, CT: Yale University Press. (paperback) Sternberg, R. J. (1986). Construct validation of a triangular theory of love. Manuscript in preparation. Sternberg, R. J., & Barnes, M. (1985). Real and ideal others in romantic relationships: Is four a crowd? Journal of Personality and Social Psychology, 49, 1586-1608. Sternberg, R. J., & Grajek, S. (1984). The nature of love. Journal of Personality and Social Psychology, 47, 312-329. Siswantoro. (2005). Metode Penelitian Sastra: Analisis Psychology. Surakarta: Muhammadiyah University Press. Suprakatiknya, A. (2009). Teori Teori Psikodinamik. Yogyakarta: Kanisius. Weihui, Z. (1999). Shanghai Baby. China: Pockets Books Yusuf, S., & Nurihsan, A. J. (2007). Teori Kepribadian. Bandung: PT Remaja Rosdakarya.